Post Yttrium-90 Imaging - Rice, Mitchell; Krosin, Matthew; Haste, Paul (Seminars in Interventional Radiology, 2021)
Transarterial radioembolization with yttrium-90 (90Y) is a mainstay for the treatment of liver cancer. Imaging the distribution following delivery is a concept that dates back to the 1960s. As β particles are created during 90Y decay, bremsstrahlung radiation is created as the particles interact with tissues, allowing for imaging with a gamma camera. Inherent qualities of bremsstrahlung radiation make its imaging difficult. SPECT and SPECT/CT can be used but suffer from limitations related to low signal-to-noise bremsstrahlung radiation. However, with optimized imaging protocols, clinically adequate images can still be obtained. A finite but detectable number of positrons are also emitted during 90Y decay, and many studies have demonstrated the ability of commercial PET/CT and PET/MR scanners to image these positrons to understand 90Y distribution and help quantify dose. PET imaging has been proven to be superior to SPECT for quantitative imaging, and therefore will play an important role going forward as we try and better understand dose/response and dose/toxicity relationships to optimize personalized dosimetry. The availability of PET imaging will likely remain the biggest barrier to its use in routine post-90Y imaging; thus, SPECT/CT imaging with optimized protocols should be sufficient for most posttherapy subjective imaging.
Keywords: yttrium-90; bremsstrahlung; SPECT; PET; imaging; interventional radiology; radioembolization